Analisis Jumlah Wajib Pajak Pph OP Yang Tidak Menyampaikan SPT Dengan Penerimaan Pajak Pada KPP Pratama Jakarta Duren Sawit - Suleman, Dede (Universitas Bina Sarana Informatika, 2019)
Personal income tax is one of the potential tax receipts in this study which will provide a percentage picture of taxpayers who do not submit SPT with the percentage of Op tax PPh revenue. it was found that the number of taxpayers who did not submit annual tax returns decreased in 2017 to only 9.4% of the taxpayers who did not submit tax returns, which meant that the public began to realize their SPT every year. tax that turns out to be known that every year there is an increase in 2017 compared to 2016 experiencing an increase of 72% and the largest revenue occurred in 2017 amounting to 89% of the set target.